Social Cognition as a Theory of Values (W. Windelband, H. Rickert) - Karosas, Justinas (Problemos, 2000)
Representatives of the school of neo-Kantianism, in their opposition to the positivism, take into account that the life of society is the sphere of realisation of aspirations and goals of individuals. Therefore, the priority is given to the values-based rather than statement- based approach. Recognition of the value-based approach in the interpretation of history introduces an element of complication into the traditional concept of cognition. Not only the objectivity of knowledge and contents, but their practical application, too, becomes problematic. The paradigm of classical thinking “knowledge is power” can be applied in practice in the life of society only very conditionally and to a limited extent. Primarily because the direct and universal linkage between knowledge and the obligation to know is missing. The above mentioned conclusions of the neo-Kantian represent a serious attack on the classical concept of cognition. The natural and social sciences therefore come to stand in an obvious opposition. This situation of opposition is a transitional phenomenon paving the way for the synthesising concepts in philosophy.